2006
DOI: 10.1136/jmg.2005.040212
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of germline rearrangements to the spectrum of BRCA2 mutations

Abstract: The molecular diagnosis of breast cancer predisposition should include screening for BRCA2 rearrangements, at least in families with a high probability of BRCA2 defects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
2
9

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 10 publications
2
34
2
9
Order By: Relevance
“…Kwong et al (17) showed that the rearrangement rate was 8.7% in the Chinese population. French and Czech population frequencies were 6-7.7%, and a high frequency of BRCA2 gene rearrangements was determined in the French population (15). Rearrangement frequencies were between 3-3.7% in Australian and Korean populations (9,13).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Kwong et al (17) showed that the rearrangement rate was 8.7% in the Chinese population. French and Czech population frequencies were 6-7.7%, and a high frequency of BRCA2 gene rearrangements was determined in the French population (15). Rearrangement frequencies were between 3-3.7% in Australian and Korean populations (9,13).…”
Section: Discussionmentioning
confidence: 91%
“…Most (25/27) rearrangements were found in patients with hereditary ovarian cancer (7). The rearrangement ratio (40.9%) given by Aktaş et al (7) for patients with ovarian cancer who had family histories was very high according to the international literature (4,(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). The second study investigated the rearrangement ratio in patients with hereditary breast cancer, but with a small sample size.…”
Section: Discussionmentioning
confidence: 97%
“…Screening for large genomic rearrangements of BRCA1 was performed for all probands with a combination of the multiplex ligation-dependent probe amplification method and the quantitative multiplex PCR of short fluorescent fragment method. 11,12 These analyses failed to reveal obviously pathogenic mutations. All patients and controls gave signed informed consent.…”
Section: Patients and Methods Patientsmentioning
confidence: 99%
“…Women who have inherited mutations in the BRCA1 or BRCA2 (BRCA1/2) genes have substantially increased risk of breast cancer, with a lifetime risk of 56% to 84% (14)(15)(16)(17). A majority of the BRCA1/2 mutations reported cause protein truncation through indels, nonsense mutations, splice variants or rearrangements (18)(19)(20)(21). A large number of sequence variants with unknown effect on the phenotype have also been detected in BRCA1/2, and several studies have tried to determine their clinical significance (22,23).…”
Section: Introductionmentioning
confidence: 99%